Sharp Bound of the Number of Zeros for a Liénard System with a Heteroclinic Loop. (28th January 2021) - Cai, Junning; Wei, Minzhi; Pang, Guoping
Abstract : In the presented paper, the Abelian integral I h of a Liénard system is investigated, with a heteroclinic loop passing through a nilpotent saddle. By using a new algebraic criterion, we try to find the least upper bound of the number of limit cycles bifurcating from periodic annulus.